A Study on the Dynamics of Indonesian Judicial Power After 1945 Constitution Amendments - et al., Udiyo Basuki (International Journal of Advanced Science and Technology, 2019)
Structural terms very clearly seen in Article 24 UUD 1945 which determines the board of Judicial Power is not only done by the Supreme Court, but also by the Constitutional Court. Moreover describes the segregation of duties and authority of the board second. While functionally, can be seen from the new functions and authority held by the board, either the Supreme Court or the Constitutional Court clearly did not have before the amendment. The 1945 Constitution amendments have been carried out four times in the period of 1999-2002. Furthermore, the four-time changes to the 1945 Constitution; the first change was through the General Session of the People’s Consultative Assembly (MPR) and the second, third and fourth changes were through the Annual Session of the People’s Consultative Assembly (MPR). In the third amendment of the 1945 Constitution, the fourth goal was the form of change experienced by the judiciary institution, or could be referred to the institution of judicial power.